ISSUES OF INTERNATIONAL COOPERATION AND MUTUAL LEGAL ASSISTANCE IN PREVENTING AND COMBATING CRIMES COMMITTED USING INFORMATION SYSTEMS (TECHNOLOGIES) - Kudratov, Bunyod (Journal of Fundamental Studies, 2026)
This article analyzes contemporary trends in crimes committed through the use of information technologies, their transnational nature, and the significance of international cooperation and mutual legal assistance mechanisms in combating such crimes. The study substantiates that the expansion of cybercrime is closely linked to the rapid development of the digital economy, electronic commerce, and digital services. It also examines mechanisms of cooperation between states within the framework of international legal instruments, including the United Nations Convention against Transnational Organized Crime, the Budapest Convention on Cybercrime, and other regional agreements. The article analyzes the main forms of international cooperation in combating cybercrime, including legal and regulatory cooperation, scientific and technical collaboration, and the exchange of information. Based on the findings of the study, a number of scientific and practical recommendations are proposed, including improving procedures for handling electronic evidence, digitalizing mutual legal assistance processes, establishing rapid information-exchange channels, and forming joint investigative teams. These measures are expected to enhance the effectiveness of efforts to prevent and combat cybercrime.